2017
DOI: 10.1037/tra0000218
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in Latina women: Examining the efficacy of the Moms’ Empowerment Program.

Abstract: This adaptation of a program designed to reduce problems associated with experiencing IPV addressed several mental health treatment needs for Latinas, particularly the need for services in Spanish. These findings demonstrate that it is possible to tailor current treatment programs for IPV in ways that are both effective and culturally sensitive. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 57 publications
(94 reference statements)
0
41
0
Order By: Relevance
“…We included 116 studies (115 papers) in the systematic review. Of these, 50 were conducted in hospital settings , 24 were delivered in a community setting , seven were delivered in military clinics for veterans or active military personnel [103][104][105][106][107][108][109], five were conducted in refugee camps [110][111][112][113][114], four used remote delivery via web-based or telephone platforms [115][116][117][118], four were conducted in specialist trauma clinics [119][120][121][122], two were delivered in home settings [123,124], and two were delivered in primary care clinics [125,126]; clinical setting was not reported in 17 studies [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 116 studies (115 papers) in the systematic review. Of these, 50 were conducted in hospital settings , 24 were delivered in a community setting , seven were delivered in military clinics for veterans or active military personnel [103][104][105][106][107][108][109], five were conducted in refugee camps [110][111][112][113][114], four used remote delivery via web-based or telephone platforms [115][116][117][118], four were conducted in specialist trauma clinics [119][120][121][122], two were delivered in home settings [123,124], and two were delivered in primary care clinics [125,126]; clinical setting was not reported in 17 studies [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Eighteen RCTs (n = 933 participants) of psychological interventions that measured the primary outcome with CAPS were included in the NMA [29, 36, 39, 44, 59, 68, 84, 88, 91-93, 100, 106, 107, 109, 116, 120, 123]. The complex-trauma subgroups of the included studies were categorised as follows: post-combat deployment veterans (55 studies) [ [31,92,93,131,137]; and mixed presentation (4 studies) [78,85,105,130]. The mean age of participants in the included RCTs was 42.6 ± 9.3 years, and 42% were male (S1 Table).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…With the success of MEP in other communities, several studies have tailored the implementation of MEP for Latina mothers. Galano et al (2017) adapted MEP for Latina mothers with a focus on PTSD. To tailor the program implementation to the Latina community, the research team took some years to establish rapport with community service agencies and known stakeholders to better understand the needs of Latinas who have been exposed to IPV.…”
Section: Intervention Programs and Their Efficacy With Latina Survivorsmentioning
confidence: 99%
“…IPV can disrupt the caregiver-child relationship and is especially toxic for young children who are exposed to violence, as it damages the perception of the caregiver (mother) as a reliable and safe protector (Lieberman & Van Horn, 2008). In addition, disenfranchised Latina immigrant mothers face the consequences of gender, class, racial oppression, and consequently poverty, resulting in poor access to protective systems of social support and mental health services which could otherwise mitigate developing posttraumatic stress and revictimization (Crenshaw, 2005;Galano et al, 2016). Undocumented Latina immigrants are more likely to have higher rates of IPV and involvement with the child welfare system, as compared to women who are permanent residents or citizens (Ogbonnaya, Finno-Velasquez, & Kohl, 2015).…”
Section: Immigrant Women's Experiences Of Violence Trauma and Margimentioning
confidence: 99%
“…Experiences of trauma, violence, and poor mental health complicate the circumstances and barriers for attaining reproductive justice among Latina immigrant women. They may be at increased risk for intimate partner violence (IPV), as compared to other minority groups, placing them at greater risk for posttraumatic stress disorder (PTSD), lifelong health problems, and disparities (Galano, Grogan‐Kaylor, Stein, Clark, & Graham‐Bermann, ). Kaltman, Green, Mete, Shara, and Miranda () found that Latina immigrant women who had experienced IPV from rape and physical violence were at highest risk for PTSD and depression comorbidity.…”
Section: Introductionmentioning
confidence: 99%